The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1670/17-029
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Years Later: Reassessing Visual and Olfactory Cues Raccoons Use to Find Diamondback Terrapin Nests

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Researchers have reported a neutral or negative relationship between nest visitation or nest flagging and the probability of nest predation (Tuberville and Burke 1994, O'Grady et al 1996, Burke et al 2005, Edmunds et al 2018), so we do not think that our activity increased nest predation. The consistent variability in egg survival across sites appears to mirror observed recruitment patterns and suggests that observed egg survival may reflect longer‐term trends and not research‐augmented predation.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Researchers have reported a neutral or negative relationship between nest visitation or nest flagging and the probability of nest predation (Tuberville and Burke 1994, O'Grady et al 1996, Burke et al 2005, Edmunds et al 2018), so we do not think that our activity increased nest predation. The consistent variability in egg survival across sites appears to mirror observed recruitment patterns and suggests that observed egg survival may reflect longer‐term trends and not research‐augmented predation.…”
Section: Discussionmentioning
confidence: 75%
“…Researchers have reported a neutral or negative relationship between nest visitation or nest flagging and the probability of nest predation (Tuberville and Burke 1994, O'Grady et al 1996, Burke et al 2005, Edmunds et al 2018), so we do not think that our activity increased Figure 3. Mean daily temperature (A), mean daily minimum temperature (B), and mean daily temperature range (C) for 56 bog turtle nests with known or hypothesized incubation periods; these nests were located at 4 sites in North Carolina, USA, 2016-2017 (site A = 20 nests; site B = 10 nests; site D = 19 nests; site H = 7 nests).…”
Section: Discussionmentioning
confidence: 83%
“…8 pieces of dried dog food). Previous research has reported no negative impact of human scent or trail cameras on wild raccoons’ willingness to approach materials manufactured and handled by humans (Munoz et al 2014 ; Edmunds et al 2018 ).…”
Section: Methodsmentioning
confidence: 92%
“…clutches eaten, empty nests and nests ignored) declined ( figure 3 a ). Simultaneously, bears showed a marginal increase in their visits to empty nests (contrary to predictions; figures 2 a and 3 b ), suggesting that the proportion of ‘nest visits’ are increasingly empty, which may indicate that bears are unable to discern full from already-predated nests in advance of visiting them [ 50 ], either by using sensory mechanisms such as the odour of a clutch or conspicuousness of eggs [ 49 ]. Given that visiting empty nests can be both time and energetically costly (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we examined whether foraging bears are responsive to declining resource density by sampling the area and exhibiting behaviours in accordance with expectations of OFT that would minimize net energetic expenditure. Specifically, by (i) using nest site information, such as the odour of a clutch or conspicuousness of eggs [ 49 ], to avoid ‘already predated’ nests [ 50 ] since foraging in an already-searched-area is both time and energetically costly and may have implications on patch-residency time decisions (i.e. marginal value theorem [ 51 , 52 ]).…”
Section: Introductionmentioning
confidence: 99%